2016
DOI: 10.1016/j.apenergy.2016.08.081
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of granular phase change materials for thermal energy storage applications in fluidized beds

Abstract: Granular PCMs are tested in 3D and 2D fluidized beds. Density, particle size and angle of repose were measured for different granular PCMs. DSC measurements confirm that there is no loss of material after fluidization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…For some samples they observed that at certain temperatures, the particles agglomerated, in a similar manner that Izquierdo- Barrientos et al (2016d) observed for granular PCMs. Although Diago et al (2018) indicated that the agglomeration was soft, it can provoque the defluidization of the bed.…”
Section: Direct Particle Radiationsupporting
confidence: 75%
See 3 more Smart Citations
“…For some samples they observed that at certain temperatures, the particles agglomerated, in a similar manner that Izquierdo- Barrientos et al (2016d) observed for granular PCMs. Although Diago et al (2018) indicated that the agglomeration was soft, it can provoque the defluidization of the bed.…”
Section: Direct Particle Radiationsupporting
confidence: 75%
“…Another application of heat storage in a fluidized bed of PCM was stud-ied by Belmonte et al (2016), who conducted TRNSYS simulations of the heating system of a single-family house consisting of a solar air heater integrated with a fluidized bed energy storage unit that contained the same granular PCM employed by Izquierdo-Barrientos et al (2016d). Figure 46 shows the schematic of the system simulated.…”
Section: Applications and Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the measured heat transfer coefficients to a horizontal cylindrical surface immersed in the bed were higher for the fluidized bed than for the fixed bed and for a granular PCM bed than for a bed of sand used as a reference material [12]. The tested granular PCM, which had a phase change temperature of approximately 50 C, did not present agglomeration problems, and although it suffered some attrition after 75 h of continuous operation with 15 charging-discharging cycles, no evidence of PCM loss was observed, and the energy storage capacity of the fluidized particles was unaffected [13].…”
Section: Introductionmentioning
confidence: 95%